1 / 44

How to convert a left linear grammar to a right linear grammar

How to convert a left linear grammar to a right linear grammar. Roger L. Costello May 28, 2014. Objective. This mini-tutorial will answer these questions: What is a linear grammar? What is a left linear grammar? What is a right linear grammar?. Objective.

hea
Télécharger la présentation

How to convert a left linear grammar to a right linear grammar

An Image/Link below is provided (as is) to download presentation Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author. Content is provided to you AS IS for your information and personal use only. Download presentation by click this link. While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server. During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

Presentation Transcript


  1. How to convert a left linear grammar to a right linear grammar Roger L. Costello May 28, 2014

  2. Objective This mini-tutorial will answer these questions: • What is a linear grammar? What is a left linear grammar? What is a right linear grammar?

  3. Objective This mini-tutorial will answer these questions: • What is a linear grammar? What is a left linear grammar? What is a right linear grammar? • Left linear grammars are evil – why?

  4. Objective This mini-tutorial will answer these questions: • What is a linear grammar? What is a left linear grammar? What is a right linear grammar? • Left linear grammars are evil – why? • What algorithm can be used to convert a left linear grammar to a right linear grammar?

  5. Linear grammar • A linear grammar is a context-free grammar that has at most one non-terminal symbol on the right hand side of each grammar rule. • A rule may have just terminal symbols on the right hand side (zero non-terminals). • Here is a linear grammar: S → aA A → aBb B → Bb

  6. Left linear grammar • A left linear grammar is a linear grammar in which the non-terminal symbol always occurs on the left side. • Here is a left linear grammar: S → Aa A → ab

  7. Right linear grammar • A right linear grammar is a linear grammar in which the non-terminal symbol always occurs on the right side. • Here is a right linear grammar: S → abaA A → ε

  8. Left linear grammars are evil • Consider this rule from a left linear grammar:A → Babc • Can that rule be used to recognize this string:abbabc • We need to check the rule for B:B → Cb | D • Now we need to check the rules for C and D. • This is very complicated. • Left linear grammars require complex parsers.

  9. Right linear grammars are good • Consider this rule from a right linear grammar:A → abcB • Can that rule be used to recognize this string:abcabb • We immediately see that the first part of the string – abc – matches the first part of the rule. Thus, the problem simplifies to this: can the rule for Bbe used to recognize this string : abb • Parsers for right linear grammars are much simpler.

  10. Convert left linear to right linear Now we will see an algorithm for converting any left linear grammar to its equivalent right linear grammar. left linear right linear S → Aa A → ab S → abaA A → ε Both grammars generate this language: {aba}

  11. May need to make a new start symbol The algorithm on the following slides assume that the left linear grammar doesn’t have any rules with the start symbol on the right hand side. • If the left linear grammar has a rule with the start symbol S on the right hand side, simply add this rule:S0→ S

  12. Symbols used by the algorithm • Let S denote the start symbol • Let A, B denote non-terminal symbols • Let p denote zero or more terminal symbols • Let ε denote the empty symbol

  13. Algorithm • If the left linear grammar has a rule S → p, then make that a rule in the right linear grammar • If the left linear grammar has a rule A →p, then add the following rule to the right linear grammar: S →pA • If the left linear grammar has a rule B →Ap, add the following rule to the right linear grammar: A →pB • If the left linear grammar has a rule S →Ap, then add the following rule to the right linear grammar: A →p

  14. Convert this left linear grammar left linear S → Aa A → ab

  15. Right hand side has terminals left linear right linear S → Aa A → ab S → abA 2) If the left linear grammar has this rule A → p, then add the following rule to the right linear grammar: S →pA

  16. Right hand side of S has non-terminal left linear right linear S → Aa A → ab S → abA A → a 4) If the left linear grammar has S →Ap, then add the following rule to the right linear grammar: A → p

  17. Equivalent! left linear right linear S → Aa A → ab S → abA A → a Both grammars generate this language: {aba}

  18. Convert this left linear grammar original grammar left linear S → Ab S → Sb A → Aa A → a S0→ S S → Ab S → Sb A → Aa A → a make a new start symbol Convert this

  19. Right hand sidehas terminals right linear left linear S0→ aA S0→ S S → Ab S → Sb A → Aa A → a 2) If the left linear grammar has this rule A → p, then add the following rule to the right linear grammar: S →pA

  20. Right hand side has non-terminal right linear left linear S0→ aA A → bS A → aA S → bS S0→ S S → Ab S → Sb A → Aa A → a 3) If the left linear grammar has a rule B →Ap, add the following rule to the right linear grammar: A →pB

  21. Right hand sideof start symbol has non-terminal right linear left linear S0→ aA A → bS A → aA S → bS S → ε S0→ S S → Ab S → Sb A → Aa A → a 4) If the left linear grammar has S →Ap, then add the following rule to the right linear grammar: A → p

  22. Equivalent! right linear left linear S0→ aA A → bS A → aA S → bS S → ε S0→ S S → Ab S → Sb A → Aa A → a Both grammars generate this language: {a+b+}

  23. Will the algorithm always work? • We have seen two examples where the algorithm creates a right linear grammar that is equivalent to the left linear grammar. • But will the algorithm always produce an equivalent grammar? • Yes! The following slide shows why.

  24. Generate string p • Let p = a string generated by the left linear grammar. • We will show that the grammar generated by the algorithm also produces p.

  25. Case 1: the start symbol produces p Suppose the left linear grammar has this rule: S → p. Then the right linear grammar will have the same rule (see 1 below). So the right linear grammar will also produce p. Algorithm: • If the left linear grammar contains S → p, then put that rule in the right linear grammar. • If the left linear grammar contains A → p, then put this rule in the right linear grammar: S →pA • If the left linear grammar contains B →Ap, then put this rule in the right linear grammar: A →pB • If the left linear grammar contains S →Ap, then put this rule in the right linear grammar: A → p

  26. Case 2: multiple rules needed to produce p Suppose p is produced by a sequence of n production rules: S →A1p1 → A2p2p1 → A3p3p2p1 →… →An-1pn-1…p3p2p1 → pnpn-1…p3p2p1 p (p is composed of n symbols)

  27. Case 2 (continued) S →A1p1 → A2p2p1 → A3p3p2p1 →… →An-1pn-1…p3p2p1 → pnpn-1…p3p2p1 Let’s see what right linear rules will be generated by the algorithm for the rules implied by this production sequence.

  28. Algorithm inputs and outputs left linear rules algorithm right linear rules

  29. Case 2 (continued) S →A1p1 → A2p2p1 → A3p3p2p1 →… →An-1pn-1…p3p2p1 → pnpn-1…p3p2p1 S → A1p1 algorithm A1→p1 (see 4 below) Algorithm: • If the left linear grammar contains S → p, then put that rule in the right linear grammar. • If the left linear grammar contains A → p, then put this rule in the right linear grammar: S →pA • If the left linear grammar contains B →Ap, then put this rule in the right linear grammar: A →pB • If the left linear grammar contains S →Ap, then put this rule in the right linear grammar: A → p

  30. Case 2 (continued) S →A1p1 → A2p2p1 → A3p3p2p1 →… →An-1pn-1…p3p2p1 → pnpn-1…p3p2p1 A1→A2p2 algorithm A2→p2A1 (see 3 below) Algorithm: • If the left linear grammar contains S → p, then put that rule in the right linear grammar. • If the left linear grammar contains A → p, then put this rule in the right linear grammar: S →pA • If the left linear grammar contains B →Ap, then put this rule in the right linear grammar: A →pB • If the left linear grammar contains S →Ap, then put this rule in the right linear grammar: A → p

  31. Case 2 (continued) S → A1p1 A1→ A2p2 S →A1p1 → A2p2p1 → A3p3p2p1 →… →An-1pn-1…p3p2p1 → pnpn-1…p3p2p1 algorithm A1→ p1 A2→p2A1

  32. Case 2 (continued) S → A1p1 A1→ A2p2 algorithm A1→ p1 A2→p2A1 From A2 we obtain p2p1: A2→ p2A1 → p2p1

  33. Case 2 (continued) S →A1p1 → A2p2p1 → A3p3p2p1 →… →An-1pn-1…p3p2p1 → pnpn-1…p3p2p1 A2→A3p3 algorithm A3→p3A2 (see 3 below) Algorithm: • If the left linear grammar contains S → p, then put that rule in the right linear grammar. • If the left linear grammar contains A → p, then put this rule in the right linear grammar: S →pA • If the left linear grammar contains B →Ap, then put this rule in the right linear grammar: A →pB • If the left linear grammar contains S →Ap, then put this rule in the right linear grammar: A → p

  34. Case 2 (continued) S → A1p1 A1→ A2p2 A2→ A3p3 S →A1p1 → A2p2p1 → A3p3p2p1 →… →An-1pn-1…p3p2p1 → pnpn-1…p3p2p1 algorithm A1→ p1 A2→p2A1 A3→ p3A2

  35. Case 2 (continued) S → A1p1 A1→ A2p2 A2→ A3p3 algorithm A1→ p1 A2→p2A1 A3→ p3A2 From A3 we obtain p3p2p1: A3→ p3A2 → p3p2A1 →p3p2p1

  36. Case 2 (continued) S →A1p1 → A2p2p1 → A3p3p2p1 →… →An-1pn-1…p3p2p1 → pnpn-1…p3p2p1 An-1→pn algorithm S →pnAn-1 (see 2 below) Algorithm: • If the left linear grammar contains S → p, then put that rule in the right linear grammar. • If the left linear grammar contains A → p, then put this rule in the right linear grammar: S →pA • If the left linear grammar contains B →Ap, then put this rule in the right linear grammar: A →pB • If the left linear grammar contains S →Ap, then put this rule in the right linear grammar: A → p

  37. Case 2 (concluded) S → A1p1 A1→ A2p2 A2→A3p3 … An-1→pn algorithm A1→ p1 A2→p2A1 A3→p3A2 … An-1→pn-1An-2 S →pnAn-1 From S we obtain pn…p2p1: S → pnAn-1 →pnpn-1An-2 →… → pnpn-1…p3A2 →pnpn-1…p3p2A1 →pn…p3pn-1p2p1 (this is the desired string, p)

  38. We have shown that for any string p generated by the left linear grammar, the right linear grammar produced by the algorithm will also generate p.

  39. How we understand the algorithm S → A1p1 A1→ A2p2 A2→A3p3 … An-1→pn These rules descend through the non-terminals until reaching a rule with terminals on the RHS, the terminals are output, then we unwind from the descent and output the terminals. algorithm A1→ p1 A2→p2A1 A3→p3A2 … An-1→pn-1An-2 S →pnAn-1 Make the rule with terminals on the RHS the starting rule and output its terminals. Ascend through the other rules.

  40. How we understand the algorithm S → A1p1 A1→ A2p2 A2→A3p3 … An-1→pn algorithm • If the left linear grammar contains A → p, then put this rule in the right linear grammar: S →pA A1→ p1 A2→p2A1 A3→p3A2 … An-1→pn-1An-2 S →pnAn-1

  41. How we understand the algorithm S → A1p1 A1→ A2p2 A2→A3p3 … An-1→pn algorithm • If the left linear grammar contains B →Ap, then put this rule in the right linear grammar: A →pB A1→ p1 A2→p2A1 A3→p3A2 … An-1→pn-1An-2 S →pnAn-1

  42. How we understand the algorithm S → A1p1 A1→ A2p2 A2→A3p3 … An-1→pn • If the left linear grammar contains S →Ap, then put this rule in the right linear grammar: A → p algorithm A1→ p1 A2→p2A1 A3→p3A2 … An-1→pn-1An-2 S →pnAn-1

  43. Left-linear grammars generate Type 3 languages • Every left-linear grammar can be converted to an equivalent right-linear grammar. • “Equivalent right-linear grammar” means the grammar generate the same language. • Right-linear grammars generate Type 3 languages. • Therefore, every left-linear grammar generates a Type 3 language.

  44. Acknowledgement The algorithm shown in these slides comes from the wonderful book: Introduction to Formal Languages by GyorgyRevesz

More Related